Pedicled transplantation of axially vascularized bone constructs in a critical size femoral defect - Arkudas, Andreas; Kneser, Ulrich (Tissue engineering, 2018)
INTRODUCTION: Axial vascularization represents a mandatory requirement for clinically applied larger scale vascularized bone grafts. The aim of this study was to combine the arteriovenous (AV) loop model in the rat with a critically sized femoral bone defect and to successfully transplant axially vascularized bone constructs into the defect. MATERIALS AND METHODS: In Groups A and C, an AV loop together with a clinically approved hydroxyapatite and beta-tricalcium phosphate (HA/β-TCP) matrix, mesenchymal stem cells, and recombinant human bone morphogenetic protein 2 were implanted into a newly designed porous titanium chamber with an integrated osteosynthesis plate in the thighs of rats, whereas in Groups B and D, the same matrix composition without AV loop and, in Group E, only the HA/β-TCP matrix were implanted. After 6 weeks, the constructs were transplanted into a 10 mm femoral defect created in the same leg, in Groups A and C, under preservation of the AV loop pedicle. Group F served as a control group with an empty chamber. Ten days (Groups A and B) and 12 weeks (Groups C-F) after transplantation, the femora together with the constructs were explanted and investigated using computed tomography (CT), micro-CT, X-ray, histology, and real-time polymerase chain reaction (RT-PCR). RESULTS: Ten days after transplantation, Group A showed a maintained vascular supply leading to increased vascularization, cell survival in the scaffold center, and bone generation compared to Group B. After 12 weeks, there was no difference detectable among all groups regarding total vessel number, although Group C, using the AV loop, still showed increased vascularization of the construct center compared to Groups D and E. In Group C, there was still enhanced bone generation detectable compared to the other groups and increased bony fusion rate at the proximal femoral stump. CONCLUSIONS: This study shows the combination of the AV loop model in the rat with a critically sized femoral defect. By maintenance of the vascular supply, the constructs initially showed increased vascularization, leading to increased bone formation and bony fusion in the long term.